Determinants of economic literacy among Russian university students: A Hierarchical Linear Modeling approach - Pavlova, Ekaterina; Kardanova, Elena; Tarovik, Elena (LPMPP Universitas Negeri Yogyakarta, 2026)
This study investigates factors influencing economic literacy among university students in Russia, addressing a significant gap in the existing literature. Economic literacy is widely recognized as a universal competency essential for navigating rapidly changing economic environments. Using a psychometrically robust Test of Economic Literacy (TEL) and a supplementary survey, the research employed Hierarchical Linear Modeling (HLM) to analyze data from 1,115 students nested within 56 academic groups across five Russian universities, accounting for both individual- and group-level influences. Key results identified academic specialization (both at high school and university levels) and individual interest in economics as the strongest positive predictors of economic literacy. Notably, receiving pocket money irregularly (vs. regularly) significantly enhanced economic literacy, suggesting adaptability benefits. Conversely, students enrolled in non-economic fields (e.g., humanities, social sciences, technical sciences, pedagogy, service/tourism) demonstrated lower levels of economic literacy compared to economics majors. Socio-demographic factors such as gender and age showed no significant effects. These findings highlight the importance of both formal academic pathways and informal experiential learning, offering insights for educators and policymakers seeking to enhance economic literacy in Russia’s evolving economic landscape.